Profil Kemampuan Pemecahan Masalah Matematika Siswa SMP pada Materi Peluang Ditinjau dari Gaya Belajar - Mufarihah, Niswatul; Yuliastuti, Rita; Nurfalah, Edy (Universitas Negeri Surabaya, 2019)
Research on profiles of mathematical problem solving ability in junior high school students on the opportunities material in terms of learning styles aimed to obtain a description of the mathematical problem solving skills based learning styles of students, that learning styles were visual, auditory, and kinesthetic. This type of research was a qualitative descriptive. The subject of research were nine students, each type of learning style consisted of 3 students. The results showed that mathematical problem solving ability of students with the type of visual learning style was superior than the students with the type of auditory and kinesthetic.